Comparative study of dexmedetomidine and tramadol for control of post-spinal anesthesia shivering - Sarwer, Fuzail; Jha, Ashutosh Kumar; Raman, Astha; Singh, Rakesh Kumar; Afroz, Danish; Hasnat, Sabir; Mohsin, Md.; Zaman, Tanveer Uz (Eastern Journal of Medical Sciences, 2016)
Background and Aim: Dexmedetomidine, a congener of clonidine is an ?2 adrenoceptor agonist, commonly used for sedation, also known to have antishivering potential. Its use as an agent to treat and control post-spinal anesthesia shivering has been inadequately studied. This study is thus aimed to evaluate the efficacy, hemodynamic changes and side effects of dexmedetomidine in comparison to tramadol when used to control post-spinal anesthesia shivering. Materials and Methods: A prospective randomized, and doubleblind study was conducted in 60 ASA Grade I and II patients of either gender, aged between 18 and 60 years, undergoing various surgical procedure under spinal-anesthesia and developing shivering. The patients were randomized into two groups of n = 30 each to receive either dexmedetomidine - 0.5 ?g/kg (Group D) or tramadol - 0.5 mg/kg (Group T) as an intravenous infusion on appearance of shivering. The time of onset, grade of shivering, time taken for cessation of shivering, response rate, and adverse effect were observed at scheduled intervals. SPSS-20 was used for statistical analysis, unpaired t-test for numerical data and chi-square test for categorical data. Results: Both the drugs effectively controlled shivering, taking almost the same time for its cessation. It was observed that patients in Group D were found to have a greater sedation score, whereas the side effects such as nausea and vomiting requiring treatment was more in Group T. The incidence of recurrence of shivering was higher in Group T. Conclusions: Dexmedetomidine effectively controls shivering taking almost the same time for cessation as that of tramadol. It provides an additional benefit of intraoperative sedation.